2002
DOI: 10.1016/s0921-4534(02)01018-3
|View full text |Cite
|
Sign up to set email alerts
|

Niobium based intermetallics as a source of high-current/high magnetic field superconductors

Abstract: The article is focused on low temperature intermetallic A15 superconducting wires development for Nuclear Magnetic Resonance, NMR, and Nuclear Magnetic Imaging, MRI, magnets and also on cryogen-free magnets. There are many other applications which would benefit from new development such as future Large Hadron Collider to be built from A15 intermetallic conductors. This paper highlights the current status of development of the niobium based intermetallics with special attention to Nb 3 (Al 1-x ,Ge x ). Discussi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…The half cell potential measurements with the reference electrode showed that the anodic potential remained at 1.5-1.6 V and the cathodic potential at *-1.5 V throughout stage 2 of the electro-deoxidation process. This confirmed that the positive deviation of the anodic and cathodic potentials in stage 2 of the galvanostatic experiment under discussion is attributable to the change of the reference electrolyte composition, and hence the transition of the electrode reaction from (15) to (17) as discussed above. The results of the ongoing studies of electro-deoxidation of TiO 2 using the new reference electrode will be discussed in detail elsewhere.…”
Section: Behaviour Of the Graphite Pseudo Reference Electrodesupporting
confidence: 77%
See 1 more Smart Citation
“…The half cell potential measurements with the reference electrode showed that the anodic potential remained at 1.5-1.6 V and the cathodic potential at *-1.5 V throughout stage 2 of the electro-deoxidation process. This confirmed that the positive deviation of the anodic and cathodic potentials in stage 2 of the galvanostatic experiment under discussion is attributable to the change of the reference electrolyte composition, and hence the transition of the electrode reaction from (15) to (17) as discussed above. The results of the ongoing studies of electro-deoxidation of TiO 2 using the new reference electrode will be discussed in detail elsewhere.…”
Section: Behaviour Of the Graphite Pseudo Reference Electrodesupporting
confidence: 77%
“…When electrons are passed into the metal oxide from an external power source, the oxygen present in the metal oxide combines with the electrons and leaves the cathode as oxygen ions which discharge at the graphite anode and liberate CO/CO 2 gas. The process was demonstrated for production of many metals [6][7][8][9][10][11][12], semi-metal [13,14] and alloys [15][16][17][18][19]. We have also investigated the electro-deoxidation behaviour of zirconium dioxide in the process [20].…”
Section: Introductionmentioning
confidence: 99%
“…[17] Many metal oxides and metaloxide mixtures have also been successfully reduced to their metals and alloys based on the cathodic oxygen ionization using molten CaCl 2 -based chlorides. [18][19][20][21][22][23][24][25][26][27][28][29][30] Little work has been published in the literature on direct electrochemical reduction of solid Al 2 O 3 and AlN in molten salts.…”
Section: B Direct Electrochemical Reductionmentioning
confidence: 99%
“…Niobium's specific characteristics like corrosion resistivity, superconductivity, thermostability and biocompatibility, make it very interesting basic or added component for alloys. Niobium alloys are successfully applied in electronic, automotive, nuclear and space industry, but also in medical aids and implants productions [1][2][3].…”
Section: Introductionmentioning
confidence: 99%